Initial Multicenter Experience With Double Nucleoside Therapy for Human Immunodeficiency Virus Infection During Pregnancy - N. S. Silverman; D. H. Watts; J. Hitti; D. M. Money; E. Livingston; J. Axelrod; J. M. Ernest; D. Robbins; M. M. DiVito (Hindawi Limited, 1998)
Objective: To study maternal and neonatal effects of combination nucleoside analog therapy administered to human immunodeficiency virus (HIV)-infected pregnant women for maternal indications.